Bioactive constituents and antibacterial screening of two Nigerian plant extracts against selected clinical bacteria (2016)
Background: The growing desires to combat antibiotic resistance among pathogenic bacteria necessitate the need to search for new antimicrobials agents from other sources such as plants. Objectives: The present study investigated the antibacterial activities and bioactive components of Nymphaea lotus and Spondias mombin against selected clinical bacteria Material and Methods: Extracts of N. lotus and S. mombin were prepared by 72 hours maceration in 70% methanol. The antimicrobial susceptibility testing (AST) of Escherichia coli, Klebsiella pneumoniae, Enterobacter aerogenes, Salmonella typhi, Staphylococcus aureus, Citrobacter freundi and, Klebsiella oxytoca against the two extracts was carried out by disk diffusion method while minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC) was by agar-well dilution and broth dilution method, respectively. The bioactive compounds of the plants were identified by Gas Chromatography-Mass Spectrometry (GC-MS) analysis. Results: Extracts of N. lotus showed better antimicrobial activities than S. mombin against all the clinical bacterial isolates with an MIC range of 3.13 – >12.5mg/mL compared to S. mombin with MIC range of 6.25 – >12.5mg/mL. The GC-MS results revealed the presence of 21 and 25 compounds for N. lotus and S. mombin respectively. Benzoic acid derivatives were in abundance in both plants with approximately 71.5% and 82.1% in N. lotus and S. mombin respectively. Conclusions: The findings from this study provided further evidence on their ethno-botanical claims and additional information on the potentials of the studied plants as effective medicinal plants with antimicrobial activity against clinical bacteria. This highlights the need for continuous exploration of medicinal plants for novel compounds with better antimicrobial property as option for the treatment of resistant bacterial infection